Legal Awareness Regarding Land Registration in Melo Village and Mandosawu District: A Comparative Socio-Legal Study - Saryono Yohanes; Rafael Rape Tupen (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
Land registration depends not only on the existence of legal regulations but also on how communities understand, evaluate, and practice the law. This issue is important because land control in East Manggarai Regency involves an interaction between customary recognition and formal land administration. This study compares the legal consciousness of residents in Melo Village and Mandosawu Urban Village regarding the registration of land ownership rights and examines the conditions associated with differences between the two locations. The study employed empirical legal research with a socio legal approach and a descriptive comparative design. Data were collected from 64 respondents, consisting of 32 residents from Melo Village and 32 residents from Mandosawu Urban Village, through questionnaires, interviews, and document analysis. The findings show that all respondents in Melo reported no knowledge or understanding of the relevant land regulations and reported no compliant behavior across the measured indicators. Positive attitudes nevertheless appeared in several indicators, especially those concerning community rights and obligations. Respondents in Mandosawu demonstrated more varied and higher levels of legal knowledge, understanding, attitude, and reported compliance. Administrative records cited in the study reported no certified land in Melo, while 47.13 percent of land parcels in Mandosawu had reportedly been certified. The study concludes that legal consciousness does not develop in a linear sequence and is associated with customary tenure systems, access to services, legal information, and the practical value of land certificates.